PENELITIAN ILMIAH BATAS WILAYAH LAUT INDONESIA BERDASARKAN KONVENSI HUKUM LAUT PBB TAHUN 1982 - Tommy Hendra Purwaka (Faculty of Law, Universitas Diponegoro, 2015)
According to UNCLOS of 1982, Indonesia has sovereignty over internal waters, archipelagic waters, and twelve nautical miles territorial sea. It has also sovereign rights over 200 nautical miles exclusive economic zones (EEZ) and continental shelves. It has not yet determined contiguous zones beyond its territorial sea. In this respect, it has duty to delimit and map maritime boundaries of its waters based on the best scientific data produced by marine scientific research. Marine scientific research, therefore, plays a very important role in the delimitation of maritime boundaries of Indonesian waters.